Tendering process / Nur Habibah Abd Rahman - Abd Rahman, Nur Habibah (Universiti Teknologi MARA UiTM,Perak, 2022)
Tender is an offer to work or supply goods at a fixed price, therefore this report will be discussing the tendering methods and procedures that are done by the company to getting project from clients. The aim of this report is to look at how department building is used, how effective it is, and how relevant it is in the tendering process. The objective of this report is to investigate the tendering process, the types of tender and to determine the problems that will occur during the process of tendering and the solution to prevent it. A tender is an invitation to tender for a project or to consider a formal offer such as a takeover bid. Tendering generally refers to the mechanism by which governments and financial institutions invite tenders for major contracts that must be presented within a time frame. This report was conducted at Casa Prima Properties Sdn. Bhd. and the methodology that has been used to collect the data and information was by the document tender and contract that have been provided by the company, by doing online research and reeding.